2017
DOI: 10.3945/ajcn.116.143016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and cardiometabolic and endocrine plasma biomarkers in US women

Abstract: Background: Healthful dietary patterns have been associated with lower risks of type 2 diabetes and coronary artery disease, but their relations with intermediate markers of cardiometabolic and endocrine health are less established. Objective: We evaluated the Dietary Approaches to Stop Hypertension (DASH), the alternate Mediterranean diet (aMED), and the Alternate Healthy Eating Index (aHEI) diet-quality scores with cardiometabolic and endocrine plasma biomarkers in US women. Design: The trial was a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…Healthy diets, including higher intake of fruits and vegetables, fish, poultry, and whole grains, have been suggested to be associated with lower risk of obesity, type 2 diabetes, and NAFLD, thereby may biologically influencing HCC risk. Additionally, all three dietary patterns have been associated with higher circulating sex‐hormone binding globulin (SHBG) levels, but lower leptin levels . A high circulating level of SHBG has been associated with increased risk of HCC, and leptin may play a role in HCG through modulation of human telomerase reverse transcriptase (a critical player of carcinogenesis) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy diets, including higher intake of fruits and vegetables, fish, poultry, and whole grains, have been suggested to be associated with lower risk of obesity, type 2 diabetes, and NAFLD, thereby may biologically influencing HCC risk. Additionally, all three dietary patterns have been associated with higher circulating sex‐hormone binding globulin (SHBG) levels, but lower leptin levels . A high circulating level of SHBG has been associated with increased risk of HCC, and leptin may play a role in HCG through modulation of human telomerase reverse transcriptase (a critical player of carcinogenesis) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all three dietary patterns have been associated with higher circulating sex-hormone binding globulin (SHBG) levels, but lower leptin levels. (40) A high circulating level of SHBG has been associated with increased risk of HCC, (41) and leptin may play a role in HCG through modulation of human telomerase reverse transcriptase (a critical player of carcinogenesis). (42) Therefore, healthy dietary patterns might influence HCC risk through their potential impact on insulin resistance and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition can contribute to development of chronic disease and cardiovascular disease 26–28 . Moreover, healthy dietary patterns have significant association between cardio‐metabolic and endocrine plasma biomarkers in United States women 32 . Thus, related factors such as nutrition that could potentially modify the association between number of teeth and MetS should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, while some studies have suggested that the association between dietary patterns and CRP levels seems to differ according to sex, [3][4][5] others have not supported this association. 6,7 Ultra-processed foods are ready-to-eat industrial formulations that are made entirely or predominantly of substances extracted from foods, food constituents or laboratory-synthesized ingredients based on organic materials. These foods present an unbalanced nutritional composition, lack micronutrients and phytochemicals, contain low levels of fiber and protein and are rich in free sugars, total fats, saturated and trans fats and sodium.…”
Section: Introductionmentioning
confidence: 99%